Fitness costs associated with 1781 and 2041 ACCase-mutant alleles conferring resistance to herbicides in Hordeum glaucum Steud. (September 2016) - Shergill, Lovreet S.; Boutsalis, Peter; Preston, Christopher; Gill, Gurjeet S.
Abstract: The amino acid substitutions that confer herbicide resistance may also involve fitness costs leaving mutant plants at a competitive disadvantage compared with wildtypes. This research investigated the effect of two target–site point mutations of ACCase gene: Ile-1781-Leu/Val and Ile-2041-Asn on plant growth and fecundity of Hordeum glaucum biotypes grown in monoculture and/or under interspecific competition in the field with Triticum aestivum L. and Lens culinaris M. The amino acid substitutions at 1781 position of ACCase gene did not impose any negative pleiotropic effects on relative growth rate (RGR), panicle emergence, plant height, total biomass, and seed production in H . glaucum mutant plants. There was some evidence for fitness cost associated with Ile-2041-Asn mutation in terms of reduced RGR and reduced vegetative biomass and seed production when grown in competition with L . culinaris . The absence of measurable negative pleiotropic effects on plant growth and fecundity associated with Ile-1781-Leu/Val ACCase mutations in H. glaucum suggest that the frequency of these alleles will not decline in the absence of herbicide selection pressure. However, the 2041-Asn allele could decrease in frequency in the absence of herbicide selection pressure. Highlights: Plants with Ile-1781-Leu/Val mutation in ACCase gene have no fitness costs. Plants with Ile-2041-Asn mutation have no fitness costs when grown with wheat. Plants with Ile-2041-Asn mutation showed fitness penalty when grown with lentils.